Study the Protective Role of Vitamin (B6 and B12) on the Some of the Blood Physiological, Biochemical Parameters and Histological Induced by Treatment of Sodium Fluoride Male White Rat - Alyaa Neamah Al-Saidi 1 , Zainab Shnewer Al-Turfi 1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study was conducted in the Faculty of Pharmacy / Karbala University for the period from 12/2018 to 7/2019. The first group was orally injected with a saline solution with a concentration of 0.9 ml and was considered as a control group. The second group was injected with sodium fluoride at a concentration of 20 mg / kg body weight (Positive), while the third group was injected with sodium fluoride with the same previous concentration with vitamin B6 leaves Group G was also injected with sodium fluoride with the same previous concentration with vitamin B12 at a concentration of 25 ?g / kg body weight. In the fifth group, sodium fluoride and vitamins B6 and B12 were injected with the same concentrations mentioned above with 1 mg / kg body weight. Ml of each of the solutions above and for all groups where the duration of the dosage lasted 21 days and once a day. a significant decrease in the ratio of body weight, red blood cells, hemoglobin, hematocrit, high density lipoprotein and glutathione peroxidase, whereas white blood cells, platelets, cholesterol, triglycerides, low density lipoproteins and Malondyaldehyde increased significantly in the sodium fluoride treatment group with control group.